2015
DOI: 10.1016/j.elspec.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitation spectrum of doped organic thin films investigated using electron energy-loss spectroscopy

Abstract: The electronic excitation spectra of undoped, and potassium as well as calcium doped phenantrene-type hydrocarbons have been investigated using electron energy-loss spectroscopy (EELS) in transmission. In the undoped materials, the lowest energy excitations are excitons with a relatively high binding energy. These excitons also are rather localized as revealed by their vanishing dispersion. Upon doping, new low energy excitation features appear in the former gaps of the materials under investigation. In K 3 pi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…Analyses of dispersion curves show that in the acenes (pentacene and tetracene) the dispersion is rather anisotropic, contrary to the phenacenes (picene and chrysene) where it is more isotropic and almost constant. As regards the phenacenes, our results corroborate the earlier stated conclusion [9,13] that the lowest-lying excitations in picene and chrysene are localized Frenkel excitons. However, we obtain that the experimental data for pentacene and tetracene can also be satisfactorily reproduced within the noninteracting exciton picture.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analyses of dispersion curves show that in the acenes (pentacene and tetracene) the dispersion is rather anisotropic, contrary to the phenacenes (picene and chrysene) where it is more isotropic and almost constant. As regards the phenacenes, our results corroborate the earlier stated conclusion [9,13] that the lowest-lying excitations in picene and chrysene are localized Frenkel excitons. However, we obtain that the experimental data for pentacene and tetracene can also be satisfactorily reproduced within the noninteracting exciton picture.…”
Section: Discussionsupporting
confidence: 91%
“…Applying the same procedure for the phenacenes picene and chrysene, we obtain the exciton dispersion within the reciprocal a * b * plane and compare it to the experimental data from [9,13] (see Figs. 6,7).…”
Section: B Picene and Chrysenementioning
confidence: 99%
See 1 more Smart Citation
“…Applying the same procedure for the phenacenes picene and chrysene, we obtain the exciton dispersion within the reciprocal š‘Ž * š‘ * plane and compare it to the experimental data from Refs. [11,15] (see Figs. 6 and 7).…”
Section: Picene and Chrysenementioning
confidence: 99%
“…Electron energy-loss spectroscopy is an experimental technique that has been recently widely used for direct measurements of the exciton band structure in aromatic hydrocarbons. [9][10][11][12][13][14][15] These experiments inspired significant theoretical work based on the first principles, i.e., starting from many-body electron-hole Hamiltonians and models based on electron-phonon interactions. [16][17][18][19][20][21][22] In the above-mentioned papers it has been suggested that exciton dispersion in organic molecular solids known as phenacenes (picene, chrysene) can be understood within the Frenkel-exciton picture, whereas the contribution of charge-transfer (CT) excitons in lowest-lying exciton states in the so-called acenes (pentacene, tetracene) is more significant.…”
Section: Introductionmentioning
confidence: 99%